L’autorité de la chose jugée, présomption légale de vérité - Sofiane Yahia Cherif (Clio@Themis)
The article explores the evolution of the concept of res iudicata authority in modern and contemporary doctrine. Res iudicata is a very ancient notion linked to the notion of truth by Ulpian, whose formula Res iudicata pro veritate accipitur (D., 1, 5, 25), was consecrated in the De regulis iuris by Justinian Law (D., 50, 17, 207). Medieval legal doctrine in the elaboration of the Romano-Canonical procedure made an appropriation of this rule. Subsequently new properties were attached to it. Domat and Pothier established a definition and a regime of res iudicata based on a presumption of legal truth. The Code civil borrowed elements from both authors in the former articles 1350 and 1351. Highly respectful exegetes focused more on the scope of the rule than on its basis. Civil doctrine since the second half of the twentieth century has challenged this conception and the attachment to the category of presumptions. Moreover, the legal regime of res iudicata has evolved under the action of the legislator and case law.